60-GHz third-order on-chip bandpass filter using GaAs pHEMT technology. (1st May 2022) - Xu, Kai-Da; Weng, Xiaoyu; Li, Jianxing; Guo, Ying-Jiang; Wu, Rui; Cui, Jianlei; Chen, Qiang
Abstract: A 60 GHz third-order on-chip bandpass filter (BPF) based on half-mode substrate integrated waveguide (HMSIW) cavity is synthesized using GaAs pHEMT technology. Two coupling slots are etched to divide the HMSIW cavity into three resonators, and then a third-order Chebyshev BPF is designed with predicted transmission zero, return loss and bandwidth through the synthesis method. The theoretical and extracted external quality factor and coupling coefficients are used to determine the dimensions of the BPF. For demonstration, a BPF sample with a bandwidth of 29.2% is fabricated, and its simulations and measurements are in good agreement.